Peran Tari Tradisional Bali Pada Kesehatan Fisik dan Psikologis: Sebuah Tinjauan Pustaka - Misyelline Lian Wijaya Gunardi; Putu Alvina Damayanti; Komang Nia Triani; Ida Bagus Yorky Brahmantya; I Gusti Ngurah Putra Eka Santosa (Aesculapius Medical Journal, 2026)
Abstract Background and Objectives: Traditional dance holds a central role in religious and customary practices, a perspective that often overshadows its potential as a beneficial physical activity for health. This perceptual gap prompted this literature review, which aims to examine the existing scientific evidence on the health benefits of Balinese traditional dance. Furthermore, this study seeks to elucidate the underlying physiological mechanisms of these positive impacts, thereby providing a robust scientific basis for its integration into health programs. Methods: A narrative review approach was utilized in this study. A structured literature search was conducted across the PubMed, Google Scholar, and ResearchGate databases. A total of nine relevant research articles were identified and selected for in-depth analysis. Results: Balinese traditional dance yields a variety of health benefits. Physically, the practice is effective in enhancing physical fitness, optimizing body composition through the reduction of subcutaneous fat, and improving cardiorespiratory system function, as reflected by increased VO?max values and vital lung capacity. These benefits are not limited to adults; in children, dance demonstrably supports the development of fundamental gross motor skills, such as balance and movement coordination. From a psychological perspective, Balinese traditional dance intervention also shows positive effects, particularly in athletes, through an enhanced ability for concentration and mental resilience. Conclusion: Balinese Traditional Dance is a culture-based physical activity modality with the potential to serve as a holistic and complementary health intervention for integration into public health promotion programs. Keywords: Traditional Dance, Health, Culture